Pengembangan Perangkat Pembelajaran Matematika Realistik Pada Konsep Pecahan Di Kelas III SD - Yuliana Batlyakru (Peneliti.net, 2022)
This research aims to generate the quality of realistic mathematics learning devices and describe realistic mathematics learning effectiveness the concept of fractions in the third grade of elementary school. This research was conducted in elementary schools YPK Ebenhaezer Timika the subjects were students in grade three A and B in the academic year 2014/2015. This type of research is descriptive research which was preceded by the development of PMR. Shape design of this study is one group pretest - posttest design and one group posttest design. The trial results showed that, PMR device produced has met the criteria of good learning, that is declared